Gingerol ameliorates neuronal damage induced by hypoxia‐reoxygenation via the miR‐210/brain‐derived neurotrophic factor axis. Issue 4 (28th December 2021) - Zhai, Yang; Liu, Bu‐Gu; Mo, Xue‐Ni; Zou, Min; Mei, Xiao‐Ping; Chen, Wei; Huang, Guo‐Dong; Wu, Lin
Abstract: The specific mechanism of gingerol in cerebral ischemia remains unknown. A neuroprotective function for miR‐210 in cerebral ischemia has been identified. The brain‐derived neurotrophic factor (BDNF)‐mediated signaling pathway protects against cerebral ischemic injury. This investigation aimed to determine whether gingerol plays a neuroprotective role in cerebral ischemia via the miR‐210/BDNF axis. N2a cells subjected to 10 h of hypoxia and 4 h of reoxygenation were treated with 5, 10, or 20 μmol/L gingerol. The levels of viability, apoptosis, and proteins in N2a cells were determined using MTT assays, flow cytometry, and western blotting, respectively. The binding relationship between BDNF and miR‐210 was studied using a dual luciferase reporter assay. The expression levels of miR‐210 and BDNF were determined using qPCR. Gingerol repressed the increase in apoptosis and decrease in viability observed in response to hypoxia/reoxygenation. Gingerol increased Bcl‐2, BDNF, and TrkB levels and reduced Bax and cleaved caspase 3 levels after hypoxia/reoxygenation. Gingerol evoked decreased expression of miR‐210. Inhibition of miR‐210 resulted in increased viability and reduced apoptosis along with increased levels of Bcl‐2, BDNF, and TrkB and reduced levels of Bax and cleaved caspase 3 after hypoxia/reoxygenation. Additionally, the miR‐210 mimic reversed changes induced by gingerol. The cotransfection of the miR‐210 mimic and wild type BDNF led to decreased luciferase activity. BDNF was negatively regulated by miR‐210. BDNF siRNA reversed these changes evoked by miR‐210 inhibition. Gingerol ameliorated hypoxia/reoxygenation‐stimulated neuronal damage by regulating the miR‐210/BDNF axis, indicating that gingerol is worthy of further application in cerebral ischemia therapy.